Adaptive Douglas–Rachford Algorithms for Biconvex Optimization Problem in the Finite Dimensional Real Hilbert Spaces - Ming-Shr Lin; Chih-Sheng Chuang (Mathematics)
In this paper, we delve into the realm of biconvex optimization problems, introducing an adaptive Douglas–Rachford algorithm and presenting related convergence theorems in the setting of finite-dimensional real Hilbert spaces. It is worth noting that our approach to proving the convergence theorem differs significantly from those in the literature.